Factors Associated with Mortality in Covid-19 Patients Hospitalized in Conakrys CT-Epi, from 2020 to 2022 (Global Journal of Medical Research, 2024)
Abstract not found
Keywords: covid-19; comorbidities; CT-Epi conakry; binary regression